Pitfalls of International Cooperative Education Programs in Vietnam - Do, Thu T (International Higher Education, 2015)
Globalization has significantly influenced the increasing international cooperative education programs between Vietnamese and foreign institutions in the last decade. For various reasons depending upon the goals and the details of these cooperative programs, the degree of success varies broadly. Some languished, some fell apart, and others required further negotiations.